2015
DOI: 10.1088/0004-637x/812/1/25
|View full text |Cite
|
Sign up to set email alerts
|

The Absolute Age of the Globular Cluster M15 Using Near-Infrared Adaptive Optics Images From Pisces/LBT

Abstract: We present deep near-infrared (NIR) J, K s photometry of the old, metal-poor Galactic globular cluster M 15 obtained with images collected with the LUCI1 and PISCES cameras available at the Large Binocular Telescope (LBT). We show how the use of First Light Adaptive Optics system coupled with the (FLAO) PISCES camera allows us to improve the limiting magnitude by ∼2 mag in K s . By analyzing archival HST data, we demonstrate that the quality of the LBT/PISCES color magnitude diagram is fully comparable with an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 96 publications
3
24
0
Order By: Relevance
“…Therefore, in Figure 7.1 we also plot the three isochrones that would correspond to the cosmic ages of 13.2, 13.7, and 14.2 Gyr in the standard model. There is a quite good convergence to the range of t 0 = (13.7 ± 0.5) Gyr coming from absolute ages of stellar systems and different classes of observations [92, 38,177]. The age predictions of our and P16 best-fit ΛCDM models perfectly agree with these, while the R18 value is pulling towards a slightly younger Universe.…”
Section: Hubble Constant Issuesupporting
confidence: 67%
“…Therefore, in Figure 7.1 we also plot the three isochrones that would correspond to the cosmic ages of 13.2, 13.7, and 14.2 Gyr in the standard model. There is a quite good convergence to the range of t 0 = (13.7 ± 0.5) Gyr coming from absolute ages of stellar systems and different classes of observations [92, 38,177]. The age predictions of our and P16 best-fit ΛCDM models perfectly agree with these, while the R18 value is pulling towards a slightly younger Universe.…”
Section: Hubble Constant Issuesupporting
confidence: 67%
“…Here we used the result of our combined analysis for the Hubble constant to compare t 0 with the estimate of the absolute ages of stellar systems (Bono et al 2010;Monelli et al 2015). There is a quite good convergence on the value t 0 = (13.7 ± 0.5) Gyr from different classes of observations (see, for a review, Freedman & Madore (2010)).…”
Section: Indirect H 0 Estimatesmentioning
confidence: 97%
“…Recently, a new tool was introduced to measure accurate star cluster parameters based on high precision infrared (IR) CMDs. Sarajedini et al (2009) and Bono et al (2010) demonstrated that the MS in a pure IR CMD exhibits a change in the color-magnitude relation of stars at ∼ 0.5 M ⊙ , with 1 Based on observations with the NASA/ESA Hubble Space Telescope, obtained at the Space Telescope Science Institute, which is operated by the Association of Universities for Research in Astronomy, Inc., under NASA contract NAS5-26555 2 Space Telescope Science Institute, 3700 San Martin Drive, Baltimore, MD 21218, USA; correnti, jkalirai, gennaro, tbrown, calamida@stsci.edu 3 Center for Astrophysical Science, John Hopkins University, Baltimore, MD 21218, USA color rapidly shifting to the blue (Pulone et al 1998(Pulone et al , 1999Zoccali et al 2000;Calamida et al 2009;Kalirai et al 2012;Milone et al 2012bMilone et al , 2014Monelli et al 2015). We will refer to this feature as the MS kink (hereafter MSK).…”
Section: Introductionmentioning
confidence: 99%